Nanocomposite of photocurable epoxy-acrylate resin and carbon nanotubes: Dynamic-mechanical, thermal and tribological properties - Dos Santos M.N.* (2013)
In this study, the thermal, dynamic-mechanical and tribological behavior of nanocomposites of a photocurable epoxy-acrylate resin and multiwalled carbon nanotubes (MWCNT) are investigated. A route consisting of a combination of sonication, mechanical and magnetic stirring is used to disperse 0.25-0.75 wt. (%) MWCNT into the resin. Two photocuring cycles using 12 hours and 24 hours of UV-A radiation are studied. The storage modulus, the loss modulus and the tan delta are obtained by dynamic mechanical analysis. Thermal stability is investigated by thermogravimetry, morphology by transmission electronic microscopy (TEM) and tribological performance using a pin-on-disk apparatus. The results indicate an increase in stiffness and higher ability to dissipate energy, as well as a shift in the glass transition temperature for the nanocomposites. The addition of nanofillers also decreased friction coefficient and wear rate of the nanocomposites but did not change the observed wear mechanisms. © 2013.